THE INFLUENCE OF AMPLITUDE AND INITIAL CONFIGURATION ON THE OCCURRENCE OF BRAZIL-NUT EFFECT ON BINARY MIXTURE OF TWO-DIMENSIONAL GRANULAR SYSTEM - Andariwulan, Wahyuni
Brazil-Nut Effect is the separation of the granular mixture consisting of two types of granular characteristics. In this mixture separation shows that when given a vibration, granules with a larger diameter or intruders can move to the surface of the container while granules with smaller diameters or granular beds go down. In this final project an observation experiment was carried out on brazil-nuts effect on a two-dimensional binary mixture with intruder with a diameter of 0.68 cm and a total of 50 granules and granular beds of 0.47 cm in diameter with 250 granules. The initial condition of the granular is varied in four conditions in terms of the intruder layer such us one horizontal layer, four horizontal layers, five vertical layers and random configuration. The experiments were carried out at a fixed frequency of 13 Hz and variations in amplitude of 0.55 cm, 0.65 cm and 0.75 cm. Brazil-nut effect is observed by reviewing changes in the position of the intruder mass center. Intruder rising time increases with increasing ?, but at ? high tends to occur mass center rotation. At an amplitude of 0.65 cm and 0.55 cm, the results of changes in the center of mass tend to be linear. At 0.75 cm amplitude, it tends to indicate the occurrence of mass center rotation so that the value of the intruder mass center of each initial condition at t = 60 s is lowest except for the conditions of five vertical layers which are higher than the amplitude of 0.55 cm.